DEVELOPMENT OF AN ECO-FRIENDLY SOLUTION FOR CHARGING POWER TOOL BATTERIES USED FOR POWER TOOLS IN MANUFACTURING - Marian Florentin Ghena; Alexandra Marina Todescu; Liviu Daniel Ghiculescu; Ovidiu Dorin Alupei Cojocariu (Nonconventional Technologies Review)
Energy security is a crucial factor in maintaining social stability, supporting everything from the operation of everyday tools to vital medical equipment. The problem of global warming, along with the decreasing availability of conventional energy sources, has intensified the search for alternative methods of energy generation. The power tool industry, which relies heavily on constant and portable power, is particularly affected by these challenges. This study aims to develop a sustainable solution for power tool batteries by creating a solar-charged battery system. The proposed system involves a storage battery integrated with a solar panel, allowing it to harness and store solar energy efficiently. This solution offers multiple benefits: it provides a renewable and ecological energy source, reduces dependence on non-renewable energy and improves the mobility and comfort of power tools by eliminating the need for constant access to traditional sockets. Addressing both environmental and practical concerns, this innovative system represents significant progress towards the development of the next generation of cordless power tools, contributing to a greener and more sustainable future. This becomes more important since power tools use is extended progressively in many manufacturing industries.